Genetics components of rice root architecture and carbon isotopic fractionation parameters: a tracer for breeding in a water-saving irrigation management - Brito, Giovani G.; Concenço, Germani; Costa, Vladimir E. [UNESP]; Fagundes, Paulo Ricardo R.; da Silva-Filho, João Luis; Parfitt, José Maria B.; Magalhães, Ariano; Silva, Giovana T.; Jardim, Thaís M.; Luccas, Nathália Furtado; Scivittaro, Walkyria B. (Springer Nature, 2022)
Phenotyping is the major bottleneck in the effort to develop varieties of rice (Oryza sativa L.) suitable for growing under a water-saving irrigation management, such as alternate wetting and drying irrigation techniques (AWD). To analyze if the genotypic variability for carbon isotope discrimination (CID) in rice leaves could be used as a relatively high-throughput tracer to early select superior genotypes highlighting improved root architecture traits when submitted to AWD, a set of twenty varieties grown under semi-natural conditions were submitted to two water irrigation regimes, continuous flooding (CF) and AWD cycles. Coefficients of genetic variance (π2g) obtained for root architecture, micro-morphological and physiological traits were significant for all of them regardless of the adopted irrigation system, except to mean root diameter. The three significant principal components (PCs) with eigenvalue > 1, explain most of the total variation across cycles and water regimes. For most of analyzed traits, the values of heritability coefficients were higher regardless of adopted irrigation management and trait category; for CID, the magnitudes of broad heritability at an individual level (greater than 0.80) were similar in the two irrigation techniques, evidencing that the success of the selection is independent of irrigation management. The higher CID values after three AWD cycles are associated with varieties with higher total root length and volume. To our knowledge, this is the first study demonstrating the potential application of CID as a tracer to select root architecture traits in rice when water-saving irrigation management is of concern.
Keywords: AWD; Carbon fractionation; Oryza sativa; Physiological breeding; Water-saving irrigation